The role of VET in a green transition of industry: A literature review - Daniel Persson Thunqvist; Maria Gustavsson; Agneta Halvarsson Lundqvist (International Journal for Research in Vocational Education and Training (IJRVET), 2023)
Purpose: This article examines the role of Vocational Education and Training (VET) in a green transition of industry. In the world of industry, battling climate change is often treated as a technical issue, but recent research on VET has tried to balance the technological paradigm with more human-centric approaches. The literature review addresses emergent VET research that presents various and partially competing perspectives on the purpose of VET in relation to climate change. Methods: We use an integrative literature review to investigate this complex topic. This technique is particularly useful for making sense of emergent research concepts, as well as various, and partially competing, theoretical and methodological approaches. It also allows us to incorporate literature from different countries and VET systems. The main search was performed in Scopus during March 2023, and included studies published within a timespan of eight years (2016-2023). Findings: Through a qualitative content analysis, we have identified five cross-cutting themes in the literature: Conceptualising ill-defined concepts of green jobs and skills; high-tech solutions in the movement towards a fourth industrial revolution versus inclusive growth for VET greening; towards sustainable work-based learning for green skills in VET; radical transformative approaches to a just green transition; and the co-creation of skill-formation ecosystems. The analysis has highlighted the ways in which VET can take on different roles in the green transition, and that these roles can be developed successively in parallel with a green transition in industry. In the development of the role of VET, it is also relevant to consider the contrast between transitional approaches and transformative approaches in VET research. While transitional approaches are recurrently marked by empirical research in specialised areas and subsystems within society, transformative approaches are characterised by a stronger focus on societal transformation (large-scale changes), power dynamics, and social justice. Conclusion: In conclusion, we suggest an analytical model that synthesises research on what role VET can play in a green transition of industry. The development model highlights that VET can take on different roles in a green transition and can gradually develop in parallel with a green transition in industry.
urn:nbn:de:gbv:18-10-1259-0
Keywords: 330; Climate Crisis; Green Transition; Industry 4.0; Vocational Education and Training; VET